Growth, Productivity and Profitability of Different Cultivars of Potato (Solanum tuberosum L.) with and without Straw-Mulch in Dadeldhura, Nepal - Thapa, Muna; Amgain, Lal Prasad; Chaudhary, Manisha (Nepalese Horticulture, 2025)
Farmers use different potato cultivars and cultivation methods, but there is a lack of information on the most suitable cultivars and techniques for optimal yields under local conditions in far western mid-hill agro-ecology of Nepal. To assess the impact of cultivars and straw mulching on the growth, yield performance and economics of potato, a field experiment was conducted during the spring, 2023 at Dotighatal, Amargadhi Municipality-03, Dadeldhura, Nepal. The experiment was laid out in two factorial Randomized Complete Block Design (RCBD) with 4 replications. Three potato cultivars (Cardinal, Desiree and Bajhang Local) were evaluated under straw-mulch and no-mulch conditions, wherein the data entry and analysis were done in MS-Excel and R-Studio, respectively. Bajhang Local exhibited the highest plant height (cm), average number of leaves and branches hill-1. But, the highest number of stems hill-1 was observed in Cardinal followed by Bajhang Local. The highest tuber yield was obtained in Cardinal (52.1 t/ha) followed by Desiree (48.0 t/ha) due to the highest weight of tubers hill-1 (1.36 kg) and number of large sized tuber (35-55 mm). Similarly, straw-mulch resulted higher yield (50.31 t/ha) than no-mulch (42.4 t/ha). However, interaction of two factor showed non-significant in both growth parameter and overall yield. This study concluded that potato cultivar Cardinal with straw-mulch was most suitable for improving the productivity, profitability and soil health of potato in the far-western mid hill agro-ecology of Nepal.